2016
DOI: 10.4103/0973-6131.171710
|View full text |Cite
|
Sign up to set email alerts
|

Impact of 10-weeks of yoga practice on flexibility and balance of college athletes

Abstract: Background:With clearer evidence of its benefits, coaches, and athletes may better see that yoga has a role in optimizing performance.Aims:To determine the impact of yoga on male college athletes (N = 26).Methods:Over a 10-week period, a yoga group (YG) of athletes (n = 14) took part in biweekly yoga sessions; while a nonyoga group (NYG) of athletes (n = 12) took part in no additional yoga activity. Performance measures were obtained immediately before and after this period. Measurements of flexibility and bal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
61
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(66 citation statements)
references
References 16 publications
4
61
0
1
Order By: Relevance
“…It's interesting in this light that the upward facing dog pose was the most popular pose among grade school students [15]. Another study measuring flexibility by joint angles suggested that after 10 weeks of yoga, a yoga group versus a nonyoga group of athletes showed increased flexibility and balance during different yoga poses including downward dog, upward dog, right foot lunge and the chair pose [27]. Yoga has been compared to other active exercise groups including calisthenics and stretchingestrengthening exercise groups.…”
Section: Physical Flexibilitymentioning
confidence: 98%
“…It's interesting in this light that the upward facing dog pose was the most popular pose among grade school students [15]. Another study measuring flexibility by joint angles suggested that after 10 weeks of yoga, a yoga group versus a nonyoga group of athletes showed increased flexibility and balance during different yoga poses including downward dog, upward dog, right foot lunge and the chair pose [27]. Yoga has been compared to other active exercise groups including calisthenics and stretchingestrengthening exercise groups.…”
Section: Physical Flexibilitymentioning
confidence: 98%
“…They have demonstrated that this sequence of preparation tends to augment lumbar spine stiffness. 4. Yoga in regular athlete training Polsgrove et al (2016) have examined the effect of yoga in athletes.…”
Section: Sport-specific Yoga Programmentioning
confidence: 99%
“…4. Yoga in regular athlete training Polsgrove et al (2016) have examined the effect of yoga in athletes. They have included yoga as an additional component in the regular athlete training and observed significant improvements in balance and flexibility.…”
Section: Sport-specific Yoga Programmentioning
confidence: 99%
See 1 more Smart Citation
“…Yoga interventions are known to affect physical health by improving muscular fitness, 5,6,36 flexibility, 2,8,22,25 increasing motor control and performance, 29,35 alter metabolism and autonomic function 35 and improve ventilatory functions of the lungs including a prolongation of breath holding time. 1,12 The practices of Asanas and pranayama are effective for improvement of strength and flexibility, enhance the joints range motions, blood circulation, and purification of the gastro-intestinal tract.…”
Section: Promotion Of Physical Healthmentioning
confidence: 99%